2011
DOI: 10.1007/s10671-011-9099-4
|View full text |Cite
|
Sign up to set email alerts
|

Can Hong Kong export its higher education services to the Asian markets?

Abstract: Internationalization becomes increasingly important in higher education in a globalized world. Exporting higher education services by recruiting overseas students is an integral facet of internationalization of higher education. It not only helps develop the place as an education hub but also facilitate internationalized environment of higher education. Alongside this global trend, Singapore, Malaysia, and Hong Kong are of no exception and have embarked on the process of internationalizing their higher educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In contrast, with a view to developing Hong Kong as an education hub and increasing competitiveness of its education services in the region, the chief executive of the Hong Kong government pledged to develop education services as a new industry for economic growth (Mok and Cheung, 2011;Tsang, 2009). Since then, the neo-liberalism characterized by market-driven and entrepreneurial values has become an overriding force in the realm of primary, secondary and tertiary education (Ng, 2011). Therefore, the item, 'education as an industry', was constructed in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, with a view to developing Hong Kong as an education hub and increasing competitiveness of its education services in the region, the chief executive of the Hong Kong government pledged to develop education services as a new industry for economic growth (Mok and Cheung, 2011;Tsang, 2009). Since then, the neo-liberalism characterized by market-driven and entrepreneurial values has become an overriding force in the realm of primary, secondary and tertiary education (Ng, 2011). Therefore, the item, 'education as an industry', was constructed in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, they became places of attraction for local talents to be internationalized at home instead of seeking opportunities in prestigious degree programs abroad. The dynamics of internationalization, however, differed in view of their legacies: that is, South Korea and Taiwan, which were more influenced by the Japanese imperial university, were more captivated than Hong Kong and Singapore by the US university model in later years (O’Sullivan, 2016; Yang, 2011). The US model could be argued to have encouraged a more entrepreneurial perspective in teaching and research than the British model did (and the differences can be seen in the Tigers’ university rankings on industrial income, as shown in Table 2).…”
Section: Tigers and Bounds: Comparative Analysismentioning
confidence: 99%
“…Once rooted into the political legacy of centralization, corporatization, and bureaucracy, universities in the Tiger economies were successful enough in shaping academic experiments for a different modeling (Mok, 2012a). Developing the East Asian space of world-class excellence is essential for local professors to feel equitably positioned for collaboration, exchange, and trading with their international counterparts and colleagues (Ng, 2011; Oleksiyenko et al, 2013; Takeda, 2020). Likewise, many non-local students report the attractiveness of not only the perceived quality of the institutions themselves, but also of the academic staff when considering their overseas study destination (Manning, 2019).…”
Section: Tigers and Bounds: Comparative Analysismentioning
confidence: 99%
“…In Hong Kong, the notion of neoliberal values in terms of economy, marketization and competition has penetrated daily operation of the school sector. It has now become a common practice for schools to contract out some of their ECAs since the mid of the 2000s where education has been regarded as an industry (Tsang, 2007) and where neo-liberal values with regard to efficiency, economy and cost-effectiveness have exerted great impacts on Hong Kong’s education services (Ng, 2011a). However, it is criticized that insertion of commercial practice into school curriculum will deviate from the chief aims of education and shape teaching and learning in a negative way (Tang, 2015; Tamatea, 2008).…”
Section: Outsourcing Ecas In Hong Kongmentioning
confidence: 99%